Crossover from lattice to plasmonic polarons of a spin-polarised electron gas in ferromagnetic EuO - Riley, JM; Caruso, F; Verdi, C; Duffy, LB; Watson, MD; Bawden, L; Volckaert, K; van der Laan, G; Hesjedal, T; Hoesch, M; Giustino, F; King, PDC (Springer Nature, 2018)
Strong many-body interactions in solids yield a host of fascinating and potentially useful physical properties. Here, from angle-resolved photoemission experiments and ab initio many-body calculations, we demonstrate how a strong coupling of conduction electrons with collective plasmon excitations of their own Fermi sea leads to the formation of plasmonic polarons in the doped ferromagnetic semiconductor EuO. We observe how these exhibit a significant tunability with charge carrier doping, leading to a polaronic liquid that is qualitatively distinct from its more conventional lattice-dominated analogue. Our study thus suggests powerful opportunities for tailoring quantum many-body interactions in solids via dilute charge carrier doping.